Age-related differences in left ventricular structure and function between healthy men and women. (3rd September 2017) - Nio, A. Q. X.; Stöhr, E. J.; Shave, R. E.
Abstract: Objectives: Cardiovascular function generally decreases with age, but whether this decrease differs between men and women is unclear. Our aims were twofold: (1) to investigate age-related sex differences in left ventricular (LV) structure, function and mechanics, and (2) to compare these measures between pre- and postmenopausal women in the middle-aged group. Methods: Resting echocardiography was performed in a cross-sectional sample of 82 healthy adults (14 young men, 19 middle-aged men, 15 young women, 34 middle-aged women: 15 premenopausal and 19 postmenopausal). Two-way ANOVAs were used to examine sex × age interactions, and t -tests to compare pre- and postmenopausal women ( α <  0.1). Results: Normalized LV mass, stroke volume and end-diastolic volume were significantly lower in middle-aged than young men, but this difference was smaller between middle-aged and young women. Peak systolic apical mechanics were significantly greater in middle-aged men than in middle-aged women, but not between young men and women. Postmenopausal women had significantly lower LV relaxation and mechanics (torsion, twisting velocity and apical circumferential strain rates) compared with middle-aged premenopausal women. Conclusion: Our cross-sectional findings suggest that the hearts of men and women may age differently, with men displaying greater differences in LV volumes accompanied by differences in apical mechanics.